“I GET BLANK WHEN START TALKING”: AN EXPLORATION TOWARDS SOURCES AND STRATEGIES OF NON-ENGLISH FRESHMEN’S ANXIETY IN ESP SPEAKING PROGRAM - Alfiani, Widya; Nurkamto, Joko; Supriyadi, Slamet (English Review: Journal of English Education, 2023)
Foreign language anxiety has been recognized as one of the foremost challenges for language learners. This study intends to explore the sources of non-English freshmen’s anxiety in ESP speaking program and their ways of dealing with it. Similarly, ESP instructors’ solutions to mitigate their freshmen’s anxiety were also discovered. A qualitative approach with an exploratory case study design was conducted to enrich insight and better understand the phenomenon. Data collection involves classroom observations and semi-structured interviews with eight non-English freshmen and two ESP instructors enrolled in ESP speaking program at a private university in Malang, East Java. The data was then analyzed thematically using the interactive model of Miles et al., (2014). It was found that speaking anxiety commonly felt by non-English freshmen was caused by some sources from freshmen’s personal mentality, linguistic capability, and classroom activity. The finding also provides several strategies adopted by freshmen to overcome their anxiety. Furthermore, various approaches implemented by ESP instructors to decrease freshmen’s speaking anxiety were offered. It should be emphasized that anxiety among students will always linger upon learning a foreign language. Still, such learning roadblocks could be diminished. Instructors possess a crucial duty to lessen the worries of learners.